Narrating Injustice Survival Self-medication by Victims of Crime - de Lint, Willem (Palgrave Studies in Victims and Victimology, 2018)
This book explores the role of self-medication in reflexive response to victimhood and victim recovery. Based on interviews, counsellor focus groups and a self-medication survey, it situates self-medication among the coping strategies that may be set in formal and informal networks. Victims primarily seek validation, and this book reviews self-medication with particular focus on how victim-survivors develop a variety of reflexive responses in their attempt to carve out a dignified response to victimization. Validation may be achieved through the pursuit of justice, but many victims suffer from multiple or complex victimisation, with limited social chances necessary to achieve a just outcome. Routines, beliefs and an ordered pathway distinguish a dignified identity and more or less successful recovery adaptations. This book also addresses the practical implications of the findings for support organisations. .